THE ANALYSIS OF STUDENTS’ LISTENING LEARNING STYLE (A STUDY OF THE 5TH SEMESTER STUDENTS AT ENGLISH EDUCATION STUDY PROGRAM OF UNIVERSITAS BENGKULU IN ACADEMIC YEAR 2018/2019) - Indri Wulandari; Alamsyah Harahap; Gita Mutiara Hati (Journal of English Education and Teaching, 2019)
This research attemted to find out the learning style used in learning listening. This research was carried out by employing descriptive quantitative design. The population of this research was the fifth semester students of English Education Study Program of University of Bengkulu in academic year 2018/2019. The samples of this research were taken by using total sampling tehcnique, i.e 79 students. The data were collected by questionnaire consisted of 36 questions related to the learning style. The questionnaire adapted from Joy Reid written in Dede Nurul Faridah (2014). The results of this study showed that the students used three types of learning style in learning listening ( visual, auditory and kinesthetic). The most used learning style was auditory (Mean score:2.85), visual (Mean score:2.75) and kinesthetic (Mean score:2.50). In conclusion, there were three learning style used in learning listening, and the most dominant learning style is auditory.